THE EFFECT OF THE PROBLEM-SOLVING LEARNING METHOD AND THE LEARNING MOTIVATION ON THE LEARNING ACHIEVEMENT IN MIDWIFERY CARE IV (PATHOLOGY) AT GIRI SATRIA HUSADA MIDWIFERY ACADEMY OF WONOGIRI - Rina Harwati (STIKES DUTAGAMA KLATEN, 2012)
Background: Midwifery Care IV (Pathology) is, on one hand, a midwifery subject matter which very much discusses about matters related to midwifery cases that need problem-solving. There have been, one the other hand, many students of midwifery academy who are unable to deal with the cases optimally, and their learning result on the subject matter has not been in compliance with the expected target. In addition, it also worsened with their low learning motivation. Objective: The objective the research is to investigate the interaction of effect between the problem-solving learning method and the learning motivation on the learning achievement in the subject matter of Midwifery Care IV (Pathology). Method: The research used a quasi experimental research method with post-test only control group design. Its population was all of the students of Giri Satria Husada Midwifery Academy of Wonogiri. The data of the research were gathered through test of achievement and questionnaire of learning motivation. Prior to their use, both the validity and reliability of the items of the instruments were tested. The items of the test of achievement were tested by using point bhiseral for their validity and KR-20 for their reliability, and those of the questionnaire of motivation were tested by using the coefficient of alpha. Analys with two way anava. Result: The result of the research shows that there is a significant interaction of effect between the problem-solving learning method and the learning motivation on the learning achievement of the students as indicated by Fcount = 11.172 with the value of p = 0.001 (p ≤ 0.05), meaning that there is a significant interaction of effect between the learning method and the learning motivation on the learning achievement in Midwifery Care IV (Pathology) of the students of Giri Satria Husada Midwifery Academy of Wonogiri. Conclusion: Based on the result of the research, conclusions are drawn that (1) the problem-solving learning method is more effective than the conventional one, and (2) the learning motivation is very influential to the learning process and the learning achievement of the students.